OPTIMASI WAKTU DAN BIAYA PADA PROYEK BENDUNGAN SELESAI (STUDI KASUS PADA PROYEK PEMBANGUNAN BENDUNGAN BENDO TAHAP 2) - Andiko Irhash Putra; Kartono Wibowo; M. Faiqun Ni’am (Jurnal Teknik Sipil dan Arsitektur, 2024)
The implementation of a project will not be separated from three factors, namely quality, time and cost. Time and cost factors can be calculated carefully and can be optimized. This needs to be done to evaluate the performance of a project, so that it becomes a lesson for the next project. This study aims to measure project performance, create optimal reschedules, optimal crash programs and calculate the time effectiveness and cost efficiency of rescheduling made in the Phase 2 Bendo Dam project. The method used in this study is the earned value and crash program with the data needed in this study is the Budget Plan (RAB), Time Schedule, Project Monthly Reports and Project Financial Reports. Then an analysis of the time and cost performance of the project is carried out, as well as calculating the optimization of alternatives for adding overtime hours and adding labor so that an optimal comparison of time and costs is obtained from the several alternatives. The results of the project performance using the earned value method in terms of costs are more accurate starting from the 18th month to the 25th month, as well as the completion time according to the planned time schedule. Meanwhile, the optimal rescheduling and crash program is adding workers with a cost efficiency of 0.66% of the total cost with a normal duration and time effectiveness of 88 calendar days.